Decoding the binary: reconsidering the hacker subculture through a gendered lens - Steinmetz, Kevin F. (Deviant behavior, 2020)
Research has demonstrated that hacker subculture - like many other tech-oriented communities - is disproportionately composed of men. While prior attempts have been made to explain this disparity, few, if any, explore the role of subculture in this gendered divide. Drawing from feminist theories, subcultural theory, and cultural criminology, this theoretical analysis examines the intersection of gender, social structure, hegemony, situated action, and subculture to argue that hacker subculture is (1) male-dominated and androcentric, (2) mired in language, like meritocratic rhetoric, which masks inequity, and (3) conducive to forms of sexual harassment and gendered exclusion. Implications for hacking research and subcultural theory are discussed throughout.